Trauma Informed Care (TIC) Interventions for Populations Experiencing Addiction and/or Homelessness: A Scoping Review of Outcomes - Dobischok, Sophia (Journal of drug issues, 2026)
Introduction: Trauma-informed care (TIC) is an expansive healthcare approach that recognizes and responds to a person’s trauma exposure. Many people experiencing a substance use disorder (SUD) and/or homelessness have trauma histories. There has not been a review of TIC intervention outcomes among these populations. Methods: A scoping review of literature (2008 to October 2023) on TIC intervention outcomes among populations experiencing SUD and/or homelessness was conducted. The search yielded 1139 texts, of which 58 met full-text extraction criteria. The final review included 32 texts that were systematically analysed. Results: TIC interventions show generally positive results for eight outcomes categories: 1) Psychological Well-being; 2) Substance Use; 3) Parenting; 4) Victimization; 5); Health; 6) Social Stability; 7) Criminal Justice; 8) and Retention/Adherence. However, these results do not consider study quality. Conclusions: TIC care approaches for populations experiencing SUD and/or homelessness have promising outcomes. Further outcome research with rigorous methodologies is needed.